2015
DOI: 10.1159/000430786
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Reversed Brain Gene Expression Changes Induced by Phencyclidine Treatment in Non-Human Primates

Abstract: The NMDA receptor antagonist phencyclidine (PCP) creates schizophrenia-like symptoms in normal controls. The effect of PCP on non-human primate brain gene expression was examined and compared to changes induced by olanzapine treatment. Experimental studies of PCP and antipsychotic drugs have direct relevance to understanding the pathophysiology and treatment of schizophrenia. Genome-wide changes in prefrontal cortex gene expression revealed alterations of 146 transcripts in the PCP treatment group compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
(32 reference statements)
2
14
0
Order By: Relevance
“…These results also support the recent cross-disorder analysis of gene expression where the mitochondrial and neuronal gene coexpression module was shared between BD and SZ cortical regions [49], and the shared genes were downregulated, independent of antipsychotic treatment [50]. …”
Section: Interaction Analysis Of Mitochondrial and Nuclear-encoded Genessupporting
confidence: 87%
See 1 more Smart Citation
“…These results also support the recent cross-disorder analysis of gene expression where the mitochondrial and neuronal gene coexpression module was shared between BD and SZ cortical regions [49], and the shared genes were downregulated, independent of antipsychotic treatment [50]. …”
Section: Interaction Analysis Of Mitochondrial and Nuclear-encoded Genessupporting
confidence: 87%
“…In a recent cross-disorder analysis of gene expression, the mitochondrial and neuronal gene coexpression module was shared between BD and SZ cortical regions [49], and the shared genes were downregulated, independent of antipsychotic treatment [50]. Not all recent studies of mitochondrial-related pathways reported an association with SZ.…”
Section: Mitochondrial Genes In the Nuclear Genome And Szmentioning
confidence: 99%
“…In these studies, APD treatment did not result in significant differences in gene expression signatures of mitochondria [97], specific RhoGTPase genes involved in dendritic spine morphogenesis [6], the immunoreactivity of MAP2 [7], or dendritic spine density in general [78]. These results were obtained from gene expression analysis of brain tissue homogenate and region-specific (but not cell-specific) imaging studies, so it is possible that APD treatment effects cannot be observed in these models without isolation or imaging co-localization of specific neuronal cell populations or subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it might reflect the drug effect that robustly changed the epigenomic state in SZ2 subjects 60 . To address this we showed no mix-up for the SZ2 samples that belong two independent subjects and that H3 K4me3 signal alterations overlap with genes showing change in expression under pharmacological induction and treatment of schizophrenia-like symptoms in primate-model (Supplementary Note, Supplementary Table 13) 61 .…”
Section: Discussionmentioning
confidence: 99%